2016
DOI: 10.5935/0100-4042.20160096
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenes Recovery of Copaiba Oil-Resin From Molecular Distillation

Abstract: publicado na web em 06/06/2016 SESQUITERPENES RECOVERY OF COPAIBA OIL-RESIN FROM MOLECULAR DISTILLATION. Copaiba oil-resin has aromatic characteristics and pharmacological activities attributed to sesquiterpenes compounds. These purified compounds present application in perfume, pharmaceutical and cosmetic industries. Therefore, the objective of this work was to use molecular distillation to recover and purify sesquiterpenes of the copaiba oil-resin with purity high. The parameters evaporator temperature (TEV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 16 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…It was concluded that a greater temperature (100 C) and lower feed flow rate (Q) (15 ml Á min À1 ), resulted in a better enrichment of sesquiterpene (98%) in the distilled stream, recovering β-caryophyllene, β-bisabolene, bergamotene, β-selinene, and α-humulene, respectively. [2] Other works involve separation based on chromatographic systems that use stationary phase (solid material) and solvents, a non-continuous process that is time-consuming and requires solvent evaporation for product purification, [66][67][68] while other work uses supercritical fluid as extraction agent. [69] From this perspective, the present study proposes a molecular distillation process for copaiba oleoresin fractioning since the terpenes constituents from copaiba oleoresin are valuable chemicals for various industries.…”
Section: Conditions Results Referencesmentioning
confidence: 99%
See 4 more Smart Citations
“…It was concluded that a greater temperature (100 C) and lower feed flow rate (Q) (15 ml Á min À1 ), resulted in a better enrichment of sesquiterpene (98%) in the distilled stream, recovering β-caryophyllene, β-bisabolene, bergamotene, β-selinene, and α-humulene, respectively. [2] Other works involve separation based on chromatographic systems that use stationary phase (solid material) and solvents, a non-continuous process that is time-consuming and requires solvent evaporation for product purification, [66][67][68] while other work uses supercritical fluid as extraction agent. [69] From this perspective, the present study proposes a molecular distillation process for copaiba oleoresin fractioning since the terpenes constituents from copaiba oleoresin are valuable chemicals for various industries.…”
Section: Conditions Results Referencesmentioning
confidence: 99%
“…The analyses for the copaiba oleoresin terpenes quantification and identification were performed by gas chromatography with a flame ionization detector (GC‐FID) (Thermo Fisher Scientific) and coupled with a mass spectrometer detector (GC–MS) (Agilent Technologies). The analysis resulted in the copaiba oleoresin ( C. officinalis ) terpenes’ total content (Figure 2) and allowed the determination of its diterpene constituents of the distilled and residue streams from the molecular distillation, as the methodology performed by Galúcio et al [ 2 ] It was possible to identify the terpene components from the mass spectrometry (NIST library), while the flame ionization detector (FID) resulted in chromatograms that allowed relating the peak areas with their contents in the sample. This analysis confirms a higher diterpenes content in the copaiba oleoresin extracted from C. officinalis (36.3% w/w), as described by Galúcio, [ 72 ] justifying its evaluation for diterpenes enrichment since other copaifera species might present lower contents of diterpenes.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations